Datos sobre el potasio - R. Elaine Turner; Linda B. Bobroff (EDIS)
This 2-page fact sheet is the Spanish language version of “Facts about Potassium” (FCS8805/FY889) Written by R. Elaine Turner and Linda B. Bobroff. Published by the UF Department of Family Youth and Community Sciences, January 2011.